Development of Story-Based Operational Learning via Visualization and Engagement (SOLVE) Instructional Material in Enhancing Procedural Fluency - Kharl O. Katigbak; Ken Aldrin P. Dilla; Kevin B. Jastiva; Cherrie Lou L. Nacar; Ivan Jade O. Burgueta (Edu Berkah Khatulistiwa, 2026)
This study focused on the development of SOLVE (Story-Based Operational Learning via Visualization and Engagement) as an instructional material to enhance Grade 7 students’ procedural fluency in algebra problem-solving in terms of efficiency, accuracy, and flexibility. A pre-experimental one-group pretest–posttest design was employed to measure students’ procedural fluency before and after the intervention of Project SOLVE. The respondents were selected Grade 7 students from Casile Integrated National High School, chosen through purposive sampling. Research-made tests were utilized to assess procedural fluency, while a Likert-scale survey measured students’ levels of visualization and engagement. Results revealed that students’ overall procedural fluency improved from the Average level to Moving Towards Mastery after the intervention. The collected data were analyzed using descriptive and inferential statistics. Paired t-tests and Wilcoxon signed-rank tests indicated significant differences between pre-test and post-test scores, showing improvements in efficiency, accuracy, and flexibility. Additionally, students demonstrated high levels of visualization and engagement, and Spearman’s correlation analysis showed a significant relationship between these factors and procedural fluency improvement. Overall, the findings highlight the effectiveness of Project SOLVE in enhancing procedural fluency in algebra. Based on these results, it is recommended that the effectiveness of Project SOLVE be further examined and validated across different grade levels and mathematical areas, particularly in relation to its impact on conceptual understanding, reasoning skills, and long-term retention.